Enhancement of Work Culture for Quality Lecturer Performance: Empirical Study - Safrudin, Safrudin; Ghazali, Al; Don Bosco Doho, Yohannes; Ali, Moh (JURNAL AL-TANZIM, 2022)
This study aims to determine whether there is an influence of work culture on the performance of lecturers at Poltekes Kemenkes III Jakarta. This study uses a quantitative approach through survey methods. The population sample is lecturers in four Departments of Health Polytechnic III Jakarta. This study indicates that work culture has a positive and significant influence on the performance of lecturers at Poltekkes Kemenkes III Jakarta. This is concluded because, from the hypothesis, the regression equation is obtained: Y = 50,135 + 0,753 X 1, which means the constant value is 50,135. From these equations, lecturer assignments can be predicted if the work culture values. The value of b = 0.753 means that the lecturer's task performance variable will increase by 75.3% if the work culture value increases by 1%. From the results of statistical tests, there is a significant relationship between workplace culture and the lecturer's task performance (p = 0.000). Moreover, the results of hypothesis testing show that the results of t arithmetic 4.651 are greater than t table 1.99 with a path coefficient of 0.365, stating that Ho is rejected and H1 is accepted.